Guidelines, Clinical Practice Recommendations, Position Papers and Consensus Statements: Definition, Preparation, Role and Application - Ingravallo, F.; Dietrich, C. F.; Gilja, O. H.; Piscaglia, F. (Ultraschall in der Medizin - European Journal of Ultrasound, 2014)
Daily clinical decisions at the bedside, rules of operation at hospitals and clinics, and health spending by governments and insurers have become more and more influenced by clinical practice guidelines (CPGs) in last years 1. Moreover CPGs are increasingly the final argument against or in favour of physicians in medical malpractice litigation. Therefore, addressing the issue of CPGs quality is now unavoidable for many specialties 234567.To this end, editorial teams of medical scientific journals have a key role in keeping and improving the quality of new CPGs 8910. Unfortunately editorial teams, particularly those belonging to subspeciality societies, may not be aware of such responsibility and may be more prone to publish CPGs without peer review 9, being exposed to an increased risk of low quality CPGs.According to the Institute of Medicine 11, CPGs are “statements that include recommendations intended to optimize patient care that are informed by a systematic review of evidence and an assessment of the benefits and harms of alternative care options”. CPGs are intended to reduce inappropriate variations in clinical care, minimize harm, promote cost-effective practice, and produce optimal health outcomes for patients, and recommendations are the guideline components that are intended to influence practitioner and patient behaviour 12.We would like to focus here on some critical steps contributing to produce guidelines and clinical practice recommendations of high quality, and to highlight some of them as a support to the ongoing works of the European Federation of Societies for Ultrasound in Medicine and Biology (EFSUMB), and its federated societies.CPGs should be systematically developed, and should report both the quality of evidence foundations and the strength of recommendations. The systems for rating quality of evidence and strength of recommendations vary somewhat according to the different bodies releasing the guidelines.For instance, the U. S. Preventive Services Task Force (USPSTF) 13 grades the quality of the overall evidence for a service on a 3-point scale (good, fair, and poor), and describes the strength of recommendations according to five levels, from A (i. e. a level according to which the USPSTF recommends that service: there is high certainty that the net benefit is substantial) to D (the USPSTF recommends against that service: there is moderate or high certainty that the service has no net benefit or that the harms outweigh the benefits). Moreover, an “I statement” is used when the “current evidence is insufficient to assess the balance of benefits and harms of the service; evidence is lacking, of poor quality, or conflicting, and the balance of benefits and harms cannot be determined”.Conversely, since 2009 the English National Institute for Health and Care Excellence (NICE) adopted the Grades of Recommendation Assessment, Development and Evaluation Working Group (GRADE) system 14, grading the quality of evidence as high, moderate, low, and very low for a particular outcome across studies 15. Despite randomized controlled trials tend to correspond to a high level of evidence, and observational studies to low, the GRADE system encompasses factors that can lower and factors that can increase the rating of the quality of evidence. For instance, grading upwards of an observational study (for example, a cohort or case-control study) may be warranted if the magnitude of the treatment effect is very large (such as severe hip osteoarthritis and hip replacement), if there is evidence of a dose-response relation or if any plausible bias would decrease, rather than increase, the magnitude of the treatment effect 16. The GRADE system offers two grades of recommendations• strong recommendation: when the desirable effects of an intervention clearly outweigh the undesirable effects, or clearly do not• weak recommendation: when the trade-offs are less certain either because of low quality evidence or because evidence suggests that desirable and undesirable effects are closely balanced 16.In keeping with the different possible approaches, it is recommended that each CPG specifies how the evidence was searched and graded, and how the recommendations were formulated, as EFSUMB did in the non hepatic applications of contrast enhanced ultrasound 17.Regardless of the grading system adopted, trustful CPGs should be systematically and transparently developed. Recognized and detailed standards for CPGs development have been established, like those issued by government agencies (e. g. the USPSTF, the NICE) or professional organizations (e. g., American College of Chest Physicians, American College of Cardiology and American Heart Association). Moreover, in recent times the GRADE has become a reference for health organizations (first of all the World Health Organization), medical journals (e. g. British Medical Journal), and professional organizations. In particular, two recent studies disclosed the benefits of the use of the GRADE system on quality of the newly released CPGs 47 issued by both the American Association for the Study of Liver Diseases and the European Association for the Study of the Liver.A further useful reference is the AGREE II 18, a 23-item checklist comprising 6 quality domains that help “guidelines developers to follow a structured and rigorous development methodology, to conduct an internal assessment to ensure that their guidance are sound, or to evaluate guidelines from other groups for potential adaptation to their own context”. AGREE II is a reliable tool widely used in the assessment of methodological rigor and transparency of CPG development 7, and can be used also by healthcare providers who wish to undertake their own assessment of a guideline 18.Whenever acknowledged development standards could not be proven, the journal should be concerned to accept the article under the term of “guideline” or “clinical practice recommendations”.On the other hand, we recall here that there are several documents, such as the “position papers”, and the “consensus” or “scientific statements”, which aim to support healthcare providers’ decision-making when the amount and/or quality of available evidence prevent to develop a CPG.A position paper designates a detailed policy report that usually explains, justifies, or suggests a particular course of action. It therefore contains also background information and discussion in order to provide a more complete understanding of the issues involved, and the rationale behind the position set forth 19. Clearly the strength of a position paper is related to that of the scientific body releasing it.A consensus statement is the product developed by an independent panel of experts, usually multidisciplinary, convened to review the research literature for the purpose of advancing the understanding of an issue, procedure, or method. It might not have a specific institutional scientific body behind despite often it is the case. At last a scientific statement represents the collective opinions of the convened expert panel 20.The value of panel multidisciplinarity should be remarked. According to Bolondi 21, all documents providing recommendations reflect the minds of the authors and their differing clinical -and technical- expertise. Indeed, converting data into recommendations requires subjective judgements 10. To avoid biased views in formulation of recommendations, multispecialty panels should include generalists and methodologists, because they possess different approaches to the same clinical problem in comparison to speciality experts, usually working in tertiary referral centre environments. Such panels should also include either patients or patient representative, because they offer different perspectives from those of clinicians and scientists 10. Methodologists and patients’ representatives could also mitigate the influence of conflicts of interest among clinician members 9.Regardless of whether the document is formally a CPG or not, medical journals should ask authors to disclose any financial conflict of interest. Norris and colleagues 22 systematically reviewed published studies addressing prevalence and effects of conflicts of interest on guidelines development. They found that from 56 % to 87 % of guidelines had authors with possible conflicts of interest with industry (consultancies, research support, equity/stock ownership). There are few data on the effect of conflicts of interest on clinical recommendations and probably they are unavoidable. However, a full transparency should be considered mandatory and could help mitigate subtle biases.Expert panels members should also be aware of intellectual conflicts of interest, which could affect researchers or reviewers too. Intellectual conflicts of interest are defined as “academic activities that create the potential for an attachment to a specific point of view that could unduly affect an individual’s judgment about a specific recommendation” 23. According to Levinsky 24, such interests are appropriate in themselves, but may conflict with the interests of research subjects and patients, and being more subtle and yet more pervasive than financial conflicts of interest they cannot be eliminated. A strategy encompassing a pivotal involvement of independent methodologists 23 has been recently adopted by the executive committee for the American College of Chest Physicians’ Antithrombotic Guidelines 25 in order to manage both financial and intellectual conflicts of interest.Finally, according to the Institute of Medicine 11, the CPG publication date, date of pertinent systematic evidence review, and proposed date for future CPG review should be documented in the CPG. Concerning updating policies, an interval of 5 years is adopted by the USPSTF, and to remain in the National Guidelines Clearinghouse a CPG must be updated at least every 5 years. As general rule, CPGs should be updated when new evidence suggests the need for modification of clinically important recommendations 11.Appropriate clinical practice recommendations may contribute to spread valid techniques, illustrating their appropriate use. In fields where enough evidence lacks, not evidence based documents, such as position papers, consensus / scientific statements may contribute. Worth to remind that lack of evidence for a certain effect does not equal evidence of lack of effect. In fact, in some fields much less efforts were devoted to produce such evidence, due to inherent difficulties, such as lack of financial support, hard to obtain gold standards, rarity of disease. Some of these instances stand particularly true in diagnostic investigations, such as ultrasonography, if compared to pharmaceutical studies.Most, but not all of the above mentioned concepts were in the minds of the expert panels which contributed to produced EFSUMB clinical practice recommendations in recent years.An effort is now recommended to improve the quality of future CPGs, which will be extended to additional ultrasound related fields and will include renewal of the currently available documents 17262728 as soon as updates will become necessary on the basis of rapidly accumulating new scientific evidence.